2015
DOI: 10.1017/s0272263115000303
|View full text |Cite
|
Sign up to set email alerts
|

Native and Nonnative Interpretation of Pronominal Forms

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…While studies looking at the L2 acquisition of null-subject languages confirm a general vulnerability for the comprehension and use of anaphoric expressions structures, it is an open question what role cross-linguistic interference plays and whether the optionality shown by the learners may be a general effect of bilingualism (see Sorace 2011 for discussion). Additionally, studies on anaphora resolution and choice of referring expressions in learners of non-null-subject languages present mixed findings (Roberts et al 2008;Wilson 2009;Ellert 2013;Contemori & Dussias 2016;2019;Schimke & Colonna 2016;Cunnings et al 2017;Contemori 2019;Contemori & Ivanova submitted). In German, where the division of labor between null and overt pronouns is present in the contrast between overt pronouns and demonstratives, Ellert (2013) and Wilson (2009) found similar interpretations of overt pronouns in L2 learners of German and in German native speakers.…”
Section: Anaphora Resolution and Choice Of Referring Expressions In Lmentioning
confidence: 99%
See 2 more Smart Citations
“…While studies looking at the L2 acquisition of null-subject languages confirm a general vulnerability for the comprehension and use of anaphoric expressions structures, it is an open question what role cross-linguistic interference plays and whether the optionality shown by the learners may be a general effect of bilingualism (see Sorace 2011 for discussion). Additionally, studies on anaphora resolution and choice of referring expressions in learners of non-null-subject languages present mixed findings (Roberts et al 2008;Wilson 2009;Ellert 2013;Contemori & Dussias 2016;2019;Schimke & Colonna 2016;Cunnings et al 2017;Contemori 2019;Contemori & Ivanova submitted). In German, where the division of labor between null and overt pronouns is present in the contrast between overt pronouns and demonstratives, Ellert (2013) and Wilson (2009) found similar interpretations of overt pronouns in L2 learners of German and in German native speakers.…”
Section: Anaphora Resolution and Choice Of Referring Expressions In Lmentioning
confidence: 99%
“…In addition, Ellert (2013) and Wilson (2009) have shown that the interpretation of demonstratives in learners of German is more indeterminate than in native speakers. In a study by Schimke and Colonna (2016), the interpretation of subject pronouns was investigated in native speakers of Turkish (a null-subject language) who learned French (a non-null-subject language) as an L2. The results showed that L2 speakers relied more on discourse cues when interpreting pronouns than native speakers.…”
Section: Anaphora Resolution and Choice Of Referring Expressions In Lmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for these results, the Interface Hypothesis (IH; e.g., Sorace, 2011) proposed that interface structures between syntax and pragmatics (as in the case of anaphoric expressions) require an increasing use of cognitive resources and are therefore less likely to be successfully acquired by bilinguals in comparison to structures without this interface. So far, research on learners of nonnull subject languages has shown conflicting results (Contemori & Dussias, 2015; Cunnings, Fotiadou, & Tsimpli, 2017; Roberts, Gullberg, & Indefrey 2008; Schimke & Colonna, 2016). For example, studies on English have demonstrated no differences between learners of English and native speakers (Contemori & Dussias, 2015; Cunnings et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on anaphora resolution and choice of referring expressions in learners of nonnull subject languages are much more limited and have shown mixed evidence (Contemori & Dussias, 2015, 2016; Cunnings et al, 2017; Ellert 2013; Roberts et al, 2008; Schimke & Colonna, 2016; Wilson, 2009).…”
Section: Introductionmentioning
confidence: 99%